Transfection efficiency of chitosan and thiolated chitosan in retinal pigment epithelium cells: a comparative study - Silva, Gabriela (2016)
Gene therapy relies on efficient vector for a therapeutic effect. Efficient non-viral vectors are sought as an alternative to viral vectors. Chitosan, a cationic polymer, has been studied for its gene delivery potential. In this work, disulfide bond containing groups were covalently added to chitosan to improve the transfection efficiency. These bonds can be cleaved by cytoplasmic glutathione, thus, releasing the DNA load more efficiently. Chitosan and thiolated chitosan nanoparticles (NPs) were prepared in order to obtain a NH3 :PO ratio of 5:1 and characterized for plasmid DNA complexation and release efficiency. Cytotoxicity and gene delivery studies were carried out on retinal pigment epithelial cells. In this work, we show that chitosan was effectively modified to incorporate a disulfide bond. The transfection efficiency of chitosan and thiolated chitosan varied according to the cell line used, however, thiolation did not seem to significantly improve transfection efficiency. The apparent lack of improvement in transfection efficiency of the thiolated chitosan NPs is most likely due to its size increase and charge inversion relatively to chitosan. Therefore, for retinal cells, thiolated chitosan does not seem to constitute an efficient strategy for gene delivery.